Segmental allergen challenge enhances chitinase activity and levels of CCL18 in mild atopic asthma. Issue 2 (18th January 2013) - Gavala, M. L.; Kelly, E. A. B.; Esnault, S.; Kukreja, S.; Evans, M. D.; Bertics, P. J.; Chupp, G. L.; Jarjour, N. N.
Summary Background Allergic airway inflammation contributes to the airway remodelling that has been linked to increased obstruction and morbidity in asthma. However, the mechanisms by which allergens contribute to airway remodelling in humans are not fully established. CCL18, chitotriosidase (CHIT1) and YKL‐40 are readily detectable in the lungs and contribute to remodelling in other fibrotic diseases, but their involvement in allergic asthma is unclear. Objective We hypothesized that CCL18, YKL‐40 and CHIT1 bioactivity are enhanced in allergic asthma subjects after segmental allergen challenge and are related to increased pro‐fibrotic and Th2‐associated mediators in the lungs. Methods Levels of CCL18 and YKL‐40 protein and chitotriosidase (CHIT1) bioactivity in bronchoalveolar lavage (BAL) fluid, as well as CCL18, YKL‐40 and CHIT1 mRNA levels in BAL cells were evaluated in patients with asthma at baseline and 48 h after segmental allergen challenge. We also examined the correlation between CCL18 and YKL‐40 levels and CHIT1 activity with the levels of other pro‐fibrotic factors and chemokines previously shown to be up‐regulated after allergen challenge. Results Chitotriosidase activity and YKL‐40 and CCL18 levels were elevated after segmental allergen challenge and these levels correlated with those of other pro‐fibrotic factors, T cell chemokines, and inflammatory cells after allergen challenge. CCL18 and YKL‐40 mRNA levels also increased in BAL cells after allergen challenge. Conclusions and Clinical Relevance Our results suggest that CCL18 and YKL‐40 levels and CHIT1 activity are enhanced in allergic airway inflammation and thus may contribute to airway remodelling in asthma.